Observations on natural regeneration in grazed Holm oak stands in the Ogliastra province (Sardinia, Italy) - Bianchi, L.; Calamini, G.; Sioni, S. (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2011)
: Observations on natural regeneration in grazed Holm oak stands in the Ogliastra province (Sardinia, Italy). This paper deals with the effects of grazing pressure in two Holm oak (Quercus ilex) stands in Ogliastra (cen tral-eastern Sardinia, Italy), with particular reference to the interactions with the natural regeneration proces ses. There is a positive interaction (facilitation) between shrubs and seedlings of tree species, as observed in other similar studies carried out by the same authors in other areas of Sardinia. Rubus ulmifolius proved to be the most efficient shrub for the protection and growth of saplings; the other shrub species play a less marked facilitating role. Although the density of shrubs hosting Holm oak seedlings is fairly high, their age and small size confirm that the current grazing pressure is incompatible with any chance of growth of the sa plings and success of the natural regeneration. The conservation of these stands must therefore rely on the rationalisation of human activities through the exploitation of a whole range of resources.
Keywords: 103-112; 2011; 665; 8; accepted; bianchi l; calamini g; citation; dell; Facilitation process; FOREST; Grazing in Forest; Holm oaks stands; http; id; in boschi di leccio; it; jan 13; jul 19; may 26; natural regeneration; ogliastra; online 2011-07-19; osservazioni sulla rinnovazione naturale; php; published online; received; sardegna; show; sioni s; sisef; soggetti a pascolo; url; www

Ethnopharmacology of ogliastra (villagrande strisaili, sardinia, Italy). - Loi, M. C.; Poli, F.; Sacchetti, G.; Selenu, M. B.; Ballero, M. (Fitoterapia, 2004)
The use of medicinal and aromatic plants was investigated in a group of 200 elderly people (60-104-year-old) from Villagrande Strisaili (Ogliastra, Sardinia, Italy), recording the use of 78 species for the treatment of various ailments, especially of the respiratory tract, the mouth, and the skin. Seventeen plants had never been described as medicinal species in peninsular Italy, while a few others turn out to have an original use for Sardinia.
The following values have no corresponding Zotero field: accession-num: 15158984
Keywords: Italy; Medicinal plants; ogliastra; Sardinia; Traditional phytotherapy; Villagrande Strisaili